Cultivating Critical Thinking Skills among Military Academy Students: -- Taking College English Course as an Example - Yang, Lin; Chong, Siwei (Transactions on Social Science, Education and Humanities Research, 2024)
In order to implement the new era's military education policy, it is essential for military academy students to possess critical thinking skills to cope with the complex and ever-changing battlefield conditions. However, the cultivation of critical thinking skills is not only a common challenge faced by higher education but also a weakness in talent development within the College English course. It is challenging for instructors to address other qualities that "high-quality" talents should possess, especially critical thinking skills, innovative abilities, and independent problem-solving capabilities. This article primarily analyzes how to enhance and cultivate critical thinking skills among military academy students within the context of College English teaching. The article first emphasizes the importance of critical thinking skills for military academy students and provides an overview of domestic and international approaches to cultivate these skills. It also identifies the challenges faced in cultivating critical thinking skills at military academies and explores methods and approaches to foster critical thinking skills from the perspectives of instructors, students, and institutions.